Pemanfaatan Personal Branding Linkedin Dalam Peningkatan Karier Mahasiswa - Salma, Erlin Alysia; Nursanti, Siti; Utamidewi, Wahyu (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
LinkedIn is a worldwide professional social network that allows users to connect with professional users around the world. LinkedIn is not just a job search platform, but also a place where individuals present themselves professionally. Students can develop their professional digital footprint through the LinkedIn platform. This research uses a constructivist paradigm with a qualitative method through a case study approach. Data collection was conducted through observation, interview, and documentation techniques. The results of this study are in the form of 3 findings, namely the communication strategies of the five informants who formed Hubert K. Rampersad's personal branding values, the career advancement of the five informants, and the communication barriers experienced by the five informants. This research is expected to build students' awareness of the potential to build LinkedIn professional personal branding as a bridge to career advancement.